Inovasi Sosial dalam Mengatasi Masalah Stunting di Lombok Barat - Pajar Hatma Indra Jaya; Saptoni Saptoni; Ahmad Izudin; Rahadiyand Aditya; Saparwadi Saparwadi; Maryani Maryani (Inovasi, 2023)
Stunting is still a social problem that the Indonesian government must resolve. The currentgovernment prioritizes one hundred districts to address the problem. Although not all stuntingprevention programs run well, one district considered capable of solving the stunting problemwell is West Lombok Regency. This research is essential because many regions in Indonesia arestill struggling to find a suitable stunting management model. This study aims to find a model forhandling stunting in this area to reduce stunting rates significantly. For this purpose, researchersconducted qualitative research by conducting interviews with the government and people of WestLombok in overcoming stunting. This study found no determinant factors that caused stunting inWest Lombok. Stunting is influenced by many factors, from health, economy, people awareness,environment-sanitation, to culture. Social protection programs in the form of conditionalassistance from the central government for the poor can also not overcome stunting. Theexistence of families receiving assistance but still experiencing stunting proves the aboveassumption. West Lombok government carried out the method of handling stunting in a top-downmanner through mainstreaming stunting handling in government programs. The Regent put a"coercion" mechanism to all agencies within the West Lombok government to create a socialinnovation program to overcome stunting. As a result, all agencies in the West Lombokgovernment have programs with unique names and ways to participate in reducing stunting. Withthis mainstreaming, everyone understands the problem of stunting and makes it a commonproblem that must be solved together so that the stunting rate in West Lombok has decreasedsignificantly.Keywords: stunting, program mainstreaming, social innovation, top-down policy, socialassistance